Radiographic imaging of metabolic bone disorders and their relative management - Chandna, Parveen; Setty J., Pramod; M. U., Jeevika; Kochar, Praveen Kumar T.; M. B., Siddesh (International Journal of Research in Medical Sciences, 2016)
Background: Bone is a strong dynamic organ of the endoskeleton playing a vital role in structural integrity envisaging to keep proper shape and maintenance of the body, mineral reservoirs, blood production, coagulation and immunity. Metabolic bone diseases are a heterogeneous group of disorders that interrupt the normal homeostasis of bone formation and resorption. Bone regulates as well as acts as a host for hematopoiesis by providing niche for proliferation and differentiation of hematopoietic cell. Bone is a dynamic tissue but metabolically active as it is being constantly formed (modelling) and reformed (remodelling). Metabolic bone diseases comprise of a broad spectrum of inherited and acquired disorders characterized by abnormalities in calcium metabolism and bone cell physiology- that lead to an altered serum calcium concentration and skeletal failure. Methods: After taking a properly informed written consent and complete history, thorough clinical examination was done and these patients were subjected to radiographic imaging and biochemical analysis. Results: Serum alkaline phosphatase is a good marker in rickets and osteomalacia, ICTP in osteoporosis, pyridinoline, deoxypyridinoline in primary hyperparathyroidism, serum PICP in renal osteodystrophy. Conclusions: In cases of rickets and osteomalacia either decreased or normal values of serum calcium and serum phosphorus were obtained. But the cases pertaining to renal failure with rickets values of serum phosphorous were found to be raised. However, in all cases of rickets and osteomalacia values of serum alkaline phosphatase were also found to be raised.